The Medicolegal Evaluation of Burns - Arısoy, Yücel; Özkara, Erdem; Vayvada, Haluk; Can, İsmail Özgür and Demiröver, Cenk and Yemişçigil, Ali (The Bulletin of Legal Medicine, 2001)
When we have taken the disability lists in forensic medicine books which are constituting reference for forming forensic reports, they suggest the most long time for echimozis (15 days), for wide 3 rd degree burns (25 days), for wide coalifying (45 days) in traumatic lesions that threats skin. In our study, our target was taking the burns for coming to an agreement between suggested times of lists and biological dates. 149 burned patients (1 st, 2 nd, 3 rd. degree) who applied to Emergency Department of Dokuz Eylül University Hospital and treated in Plastics Surgery Clinics between the time 15-02.2000 and 24.02.2001, were examined retrospectively. We have taken three patient groups by examining their files and interviews for obtaining hospitalizing time, survival time and being unable for working time because of burns to assess between datas and disability lists. Key Words: Burns, healing time, forensic medicine.